Scoping review of trials evaluating adhesive strategies in pediatric dentistry: where do simplified strategies lie? - António H. S. Delgado; Hasan Jamal; Anne Young; Paul Ashley (BMC Oral Health, 2021)
Abstract Background Adhesive restorations allow a conservative approach to caries management and are increasingly used as a restorative option in pediatric dentistry. Placement can be difficult in children because of the cooperation required for multiple bonding steps. Due to this, it is vital to assess if novel, simpler strategies have been featured in clinical trials and if clinical trials are researching the different existing adhesive strategies. Methods This review followed Preferred Reporting Items for Systematic Reviews and Meta-analysis adapted for Scoping Reviews (PRISMA-ScR) guidelines. PubMed/Medline, Cochrane Central, Scopus and EMBASE were used for systematic search, using free keywords and controlled search terms. Clinical trials of children requiring a restorative intervention which featured adhesive strategies were included. Only peer-reviewed trials of primary teeth restored with resin composites, published in the last 10-year period were eligible. Data charting was accomplished independently by two reviewers, and studies were summarized according to their date, type, intervention, sample size, observation period, outcomes and conclusions. Quality assessment was performed using Cochrane’s Risk of Bias 2.0 tool. Results 700 potentially relevant references were found, which after a rigorous inclusion scheme, resulted in a total of 8 eligible clinical trials. Out of these, 7 were randomized clinical trials. Most trials featured a split-mouth design and the observation period ranged from 12 to 36 months. The trials evaluated interventions of two self-adhesive composites, two bulk-fill composites, two novel composites, one compomer and eight adhesives from different strategies. Most studies (4/8) included were judged to raise some concerns regarding risk of bias, while two were classified as high risk and two as low. Conclusion Few studies comparing adhesive strategies were found, especially adhesives in sound substrates. The existing studies do not reflect all current approaches that could be used in pediatric dentistry. Further studies addressing bioactive composites and contemporary adhesives are necessary.